2023
DOI: 10.1136/bmjgh-2022-010850
|View full text |Cite
|
Sign up to set email alerts
|

Systematic mapping of gender equality and social inclusion in WASH interventions: knowledge clusters and gaps

Abstract: IntroductionPoor access to water, sanitation and hygiene (WASH) services threatens population health and contributes to gender and social inequalities, especially in low-resource settings. Despite awareness in the WASH sector of the importance of promoting gender equality and social inclusion (GESI) to address these inequalities, evaluations of interventions focus largely on health outcomes, while gender equality and other social outcomes are rarely included. This review aimed to collate and describe available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…We used machine learning algorithms to support the title and abstract screening stage. A detailed description of all methodological steps is available in the systematic map report [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used machine learning algorithms to support the title and abstract screening stage. A detailed description of all methodological steps is available in the systematic map report [21].…”
Section: Methodsmentioning
confidence: 99%
“…This brief provides policy-relevant insights from our comprehensive mapping of evidence of GESI outcomes related to WASH interventions [21]. Our review aimed to answer the following question: What evidence exists on the GESI outcomes of WASH interventions in low-and mid-income contexts?…”
Section: Introductionmentioning
confidence: 99%
“…Email discussions continued between the participants between workshops to help clarify ideas and insights. The workshop inputs included gender-integration experiences from other sectors (see Supplementary material), gender-WASH literature (van Wijk-Sijbesma, 1985, 1998Dery et al, 2019;MacArthur et al, 2020;Caruso et al, 2022;Macura et al, 2023), and Water for Women Fund experiences in the "Toward Transformation" strategy (Water for Women, 2019b). Relevant case examples were documented in an online database (stored in Airtable) and referred to throughout the workshops.…”
Section: Approachmentioning
confidence: 99%
“…Lastly, there are few academically published case studies describing WASH program initiatives and outcomes in relation to gender equality. Therefore, the team was required to rely heavily on historical examples (van Wijk-Sijbesma, 1985, 1998, gray literature cases known to the team, and recent gender-WASH literature reviews (van Wijk-Sijbesma, 1985, 1998Dery et al, 2019;MacArthur et al, 2020;Caruso et al, 2022;Macura et al, 2023). Future work could benefit from a systematic case study review of gender-WASH programming examples from both gray and published literature.…”
Section: Approachmentioning
confidence: 99%
“…It is evident that there is a need to achieve gender equality to make additional progress in WASH. Recent systematic reviews of interventions with GESI outcomes of projects carried out between 2010 and 2020 showed that only 22% of the studies involved interventions that “included GESI mainstreaming components” (Macura et al., 2023, p. 6). Academic analysis of gender equality principles, language, and indicators have also been conducted (Caruso et al., 2021; Dery et al., 2020; Leahy et al., 2017; MacArthur et al., 2020; Pouramin et al., 2020); these highlight the inequalities that persist across WASH.…”
Section: Introductionmentioning
confidence: 99%